Community Perceptions of Drinking Water Quality Supplied by DWASA: A Case Study of Kafrul Thana, Dhaka - Shammi, Mashura; Kanak, Shabnam Mostofa; Rahman, Md Mostafizur; Uddin, M Khabir (Jahangirnagar University Environmental Bulletin, 2013)
DOI: http://dx.doi.org/10.3329/jueb.v1i0.14547 Jahangirnagar University Environmental Bulletin, Vol.1, 41-53, 2012